Meneguhkan Kembali Etika Dalam Metode Dakwah Bil Lisan - Sudin, Mokhtaridi; Rasyid, M Ardi (Tarbawiyah Jurnal Ilmiah Pendidikan, 2022)
Da'wah is a means of broadcasting the religion of Islam that is delivered by da'wah interpreters. Every human being who embraces Islam is obliged to fulfill da'wah. Carrying out da'wah also has an ethic that must be understood by preachers, the delivery of da'wah can be channeled properly if you know the ethics. Preaching with an interesting nature, good and smooth language, gestures that are full of courtesy will also be viewed more comfortably by the object to be addressed in preaching. If the preacher does not bring the material with the right ethics, it will create an uncomfortable atmosphere, and delivery will be considered bad.